2017
DOI: 10.3389/fmicb.2017.01914
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Extended-Spectrum β-Lactamase-Producing E. coli and Vancomycin-Resistant Enterococci in the Northern Dutch–German Cross-Border Region

Abstract: Objectives: To reveal the prevalence and epidemiology of extended-spectrum β-lactamase (ESBL)- and/or plasmid AmpC (pAmpC)- and carbapenemase (CP) producing Enterobacteriaceae and vancomycin-resistant enterococci (VRE) across the Northern Dutch–German border region.Methods: A point-prevalence study on ESBL/pAmpC/CP producing Enterobacteriaceae and VRE was carried out in hospitalized patients in the Northern Netherlands (n = 445, 2012–2013) and Germany (n = 242, 2012). Healthy individuals from the Dutch communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
0
23
1
Order By: Relevance
“…Interestingly, EC121 strain belongs to ST101, which has been previously reported to be involved in nosocomial outbreaks caused by Metallo-β-lactamases-producing strains in many countries from Europe, Asia, and Oceania [ 39 , 40 , 83 , 84 , 85 ]. Furthermore, ST101 has also been detected among strains of nonoutbreak related extraintestinal infections [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ], water [ 94 ], poultry infection [ 95 ], retail food [ 86 , 96 , 97 , 98 ], and human and animal intestinal microbiota [ 93 , 99 , 100 , 101 , 102 ], mostly presenting an MDR phenotype. Shrestha et al [ 103 ] drew attention to ST101 due to the pan drug resistant (PDR) phenotype presented by some strains of this ST, and mainly because it is not considered a pandemic clone, although it has been isolated worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, EC121 strain belongs to ST101, which has been previously reported to be involved in nosocomial outbreaks caused by Metallo-β-lactamases-producing strains in many countries from Europe, Asia, and Oceania [ 39 , 40 , 83 , 84 , 85 ]. Furthermore, ST101 has also been detected among strains of nonoutbreak related extraintestinal infections [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ], water [ 94 ], poultry infection [ 95 ], retail food [ 86 , 96 , 97 , 98 ], and human and animal intestinal microbiota [ 93 , 99 , 100 , 101 , 102 ], mostly presenting an MDR phenotype. Shrestha et al [ 103 ] drew attention to ST101 due to the pan drug resistant (PDR) phenotype presented by some strains of this ST, and mainly because it is not considered a pandemic clone, although it has been isolated worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this small study suggested cross-border spread in clinical isolates. As no data was available from German community strains, no conclusion could be drawn concerning possible cross-border spread in the community [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, in these studies, phenotypic tests detecting only ESBL (not AmpC) were used. In countries of Western and Northern Europe, a prevalence of ESBL producing bacteria was low in the Netherlands (6.1%), Germany (7.7%), Sweden (2–4%), and Norway (1.5%) (Brolund et al, 2014; Soraas et al, 2014; Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%